Is gold always a safe haven? - Ryan, M.; Corbet, S.; Oxley, Leslie (2024)
This study reexamines the long-held view of gold as a universal safe haven during stock market downturns. Utilising a dataset from 1979 to 2020, we investigate the conditional nature of gold's safe-haven status with the S&P 500 index, revealing that the specific drivers of market declines determine the extent of gold's safe-haven status. Notably, gold's protective efficacy is pronounced during downturns specifically triggered by macroeconomic news but less evident in downturns triggered by other reasons. Our result challenges traditional perceptions and suggests investors adopt a contextual approach to identifying safe haven assets.